„Narody zamiast narodu”. Afrahata polemika z judaizmem - Mariusz Rosik (Wrocławski Przegląd Teologiczny)
Aphrahat, called the Persian Sage, was a Syriac-Christian of the 3-rd / 4-th century from Adiabene region of Persian Empire. He is an author of twenty-three sermons called Demonstrationes (sometimes also Homiliae). Almost half of them are concerned with the religion of Jews. It seems that some Christians in the Persian Church wanted to become Jews or to return to Judaism, or to incorporate Jewish traditions into Christianity In the article the author presents the main characteristics of Aphrahat’s view on Judaism. The Persian Sage is convinced that God had rejected one nation Israel and He choose Christians from many nations. His view on Judaism was one of the impulses to so-called theologia substitutionis.